Evaluations of beef tenderness by Warner-Bratzler shear force, a descriptive-texture profile sensory panel, and a descriptive attribute sensory panel - M.M. Otremba; Edgar Chambers IV; Michael E. Dikeman; George A. Milliken; Sally L. Stroda; John A. Unruh (Kansas Agricultural Experiment Station Research Reports, 1999)
his study examined interrelationships among Warner-Bratzler shear force (WBSF), evaluation by a highly trained descriptive-texture- profile (DTP) sensory panel, and evaluation by a trained descriptive attribute (DA) sensory panel as affected by muscle fiber orientation of samples. Eighteen longissimus lumborum and 18 semitendinosus muscles from Choice and Select carcasses were cut into 1- inch steaks and cooked to 150EF. Cores were obtained by two methods (parallel to the muscle fiber orientation and perpendicular to the cut steak surface) for WBSF determinations. Cubes ½ x ½ x 1 in. were presented to the DTP and DA sensory panels. Cores taken parallel to the longissimus muscle fiber orientation had a 1.4 lb. higher (P<.05) mean WBSF than cores taken perpendicular to the cut steak surface. Both panels detected carcass differences; however, a panelist x carcass effect (P<.05) occurred for the DA panel. Both panels detected differences (P<.05) between muscle fiber orientations for attributes related to tenderness. Muscle fiber orientation of samples may need to be parallel for WBSF but perpendicular to the steak surface for sensory panel evaluation.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Tenderness; Shear force; Sensory panels; Muscle fiber orientation